PENGARUH PERBANDINGAN STRAWBERRY DAN ANGGUR MERAH SERTA LAMA PENYIMPANAN TERHADAP MUTU INFUSED WATER (The Effect Ratio of Strawberry and Red Grape and Storage on Quality of Infused Water) - Ori Sativa Br.Sinaga; Rona J. Nainggolan; Terip Karo-Karo (Universitas Sumatera Utara, 2019)
ABSTRACInfused water was the drink made by soaking fruit in the cooled water for about a night in the refrigerator. This study was aimed to study of vitamin C content, sugar content, total microbes, pH value, total acid, total dissolved solids, and organoleptic of the infused water. This study used a Completly Randomized Design (CRD), with two factors. The first factor was the ratio of strawberries with red grapes (80:20, 60:40, 40:60, 20:80) and the second factor was the length of storage (0 days, 2 days, 4 days, 6 days, 8 days). The results showed that the combination of strawberry treatment with red wine with a ratio of 80:20 for 0 days had the best quality. The characteristics of this infused water were; vitamin C levels 7.3316 mg / 100 g; total sugar content of 9,658%; pH 4,3688; total acid 0.9140%; total dissolved solids 4,625oBrix; microbial total of 4,0250 CFU / g; hedonic color 4.14; hedonic aroma 4.36; numeric color 4.00; numerical aroma of 3.99. The length of storage and ratio of strawberries with red wine had a very significant effect on pH values, total dissolved solids, total sugar, microbial total, total acid, vitamin C levels, hedonic organoleptic values ​​of color and aroma, and organoleptic values ​​of color and aroma scores. Keywords: Infused Water, Strawberry, Red Grape. ABSTRAK Infused water adalah minuman yang dibuat dengan cara perendaman buah dalam pendingin air selama semalam di lemari es. Penelitian ini bertujuan untuk mengetahui kadar vitamin C, kadar gula total, total mikroba, pH, total asam, total padatan terlarut, dan uji organoleptik infused water. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL), dengan dua faktor. Faktor yang pertama perbandingan strawberry dengan anggur merah (80:20, 60:40, 40:60, 20:80) dan faktor yang kedua lama penyimpanan (0 hari, 2 hari, 4 hari, 6 hari, 8 hari). Hasil penelitian menunjukkan bahwa kombinasi perlakuan strawberry dengan anggur merah dengan perbandingan 80:20 selama 0 hari memiliki mutu terbaik. Karakteristik dari infused water ini yaitu; kadar vitamin C 7,3316 mg/100 g; kadar gula total 9,658%; pH 4,3688; total asam 0,9140%; total padatan terlarut 4,625oBrix; total mikroba 4,0250 CFU/g; hedonik warna 4,14; hedonik aroma 4,36; numerik warna 4,00; numerik aroma 3,99. Lama penyimpanan dan perbandingan strawberry dengan anggur merah memberi pengaruh sangat nyata terhadap nilai pH, total padatan terlarut, total gula, total mikroba, total asam, kadar vitamin C, nilai organoleptik hedonik warna dan aroma, serta nilai organoleptik skor warna dan aroma. Kata kunci : Infused Water, Strawberry, Anggur Merah.